ACHIEVING SERVICE RECOVERY THROUGH SERVICE INNOVATION: THE CRITICAL ROLE OF EMPLOYEE EMPOWERMENT - Al-Ababneh, Mukhles M.; Masadeh, Mousa A.; Al-Sabi, Samer M.; Al-Badarneh, Mohammad B. (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Research in service recovery and service innovation has attracted significant attention in recent years but few studies have focused on achieving service recovery through service innovation. The current study aims to bridge this gap in research – to investigate the effect of service innovation on service recovery. Additional emphasis is also given to examining whether employee empowerment serves as a mediator between service innovation and service recovery in the hotel industry. A quantitative survey method was applied by using a 60-item questionnaire and data collected from a sample of 381 employees from five-star hotels in Jordan. The findings confirmed the hypotheses, revealing a direct effect of service innovation on employee empowerment which, in turn, had a significant influence on service recovery. Additionally, this study proposed a model of influence of service innovation in service recovery, whereby employee empowerment fully mediates this relationship. The current study contributes to the existing literature on service innovation and service recovery as it identifies the role of service innovation in enhancing service recovery performance in hotels.